A bi-directional ultrasonic elliptical vibration actuator (BUEVA) for micro machining - Ammouri, Ali H. (2017)
Presented is the detailed design and implementation of a bi-directional ultrasonic elliptical vibration actuator (BUEVA) for micro machining. Removal of material occurs via a generated elliptical tool motion resembling a natural ‘spoon feeding’ action in contrast to in-plane, horizontal motion utilized by most existing setups. The motion is generated by two stacked ceramic multilayer actuator ring (SCMAR) piezo elements vibrating out of phase in the tool’s axial and transverse directions. The amplitude of vibration of the tool is controlled in order to vary the cutting depth according to the desired cutting parameters. To ensure precise tool positioning, the BUEVA actuator is fitted to a 3-axis precision machining center that provides the necessary tool path. The cutting forces and the resulting surface finish are both numerically modeled and then experimentally measured by a 3-axis mini dynamometer and a surface profilometer, respectively. Preliminary cutting results show good dimensional definition and surface integrity.